The Effects of Globalization on Wages, Employment, and Wage Share in Austria - Onaran, Özlem (Wirtschaft und Gesellschaft, 2008)
This paper estimates the employment and wage effects of foreign trade and Austrian outward FDI on employment, wages, and the wage share in Austria. There is evidence of significant negative effects of imports and FDI on both employment and wages. The results are not limited to workers in low skilled sectors. Particularly workers in high skilled sectors experience negative effects. There are also negative effects on white collar workers, particularly due to outward FDI. Even after we take into consideration the positive export effects, it is unlikely that exports offset negative import and FDI effects. The negative employment effect of Austria's investment abroad is primarily due to the rise in the employment in the foreign affiliates in the East. The employment in foreign affiliates in developed countries seems to have a negative effect in services only, which could be interpreted as the horizontal FDI effect. The negative wage effects are originating from affiliate employment in both the East and the developed countries in industry, but no effect is found in the total economy. There is evidence of some positive wage effect of affiliate employment in the East in services sectors. Bringing together these effects we find that the increase in employment in the foreign affiliates of Austria has resulted in a deterioration of the wage share with the effect originating from both country groups in industry, and only from the East in the total economy. Growth of value added as well as non-ICT capital has a positive effect, and technological change (the growth of ICT capital) has a negative effect on employment growth in industry. Technological change effects only blue collar workers’ employment. Technological change also results in a decline in the industry wage share. Regarding import effects, in aggregate total imports also have a negative impact on both employment and wages, and thereby on the wage share in manufacturing as well as the total economy (non-agricultural tradable sectors). The negative impact on employment is particularly due to intermediate import penetration from the East. However, intermediate import penetration from the East has a positive effect on wages (in both manufacturing and the total economy), which might be indicating that intermediate import penetration from the East has resulted in substitution of domestic employment with foreign employment, but in the meantime has resulted in skill upgrading. Intermediate import penetration from the developed countries also has a negative impact on both employment and wages in the total economy. In manufacturing as well as the total economy imports from the rest of the world have positive employment and wage effects.